The Implementation of Audio-Visual Reading Activity in the Primary Year of Metro School Makassar - Endah Pratiwi Andi; Baso Jabu; Iskandar (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
Andi Endah Pratiwi, 2024. The Implementation of Audio-visual Reading Activity in the Primary Year Metro School. Thesis. English Language Education Study Program, Graduate Program. Universitas Negeri Makassar (supervised by Baso Jabu and Iskandar). This research has four objectives: (1) to determine what factors influence Metro School Makassar's primary students' audio-visual reading activities; (2) to know how primary-year teachers implement an audio-visual reading activity; (3) to determine teachers' perceptions; and (4) to determine students' perspectives. Case study research involved teachers and students. The writer conducted research using an observation sheet and interview guide. A primary-year teacher at Metro School used a video reading activity. The Merdeka and Cambridge Primary Curricula are shaped by context, with technology as a secondary factor; the school provides LCDs and wireless networks for support. Audio-visual activities require planning, implementation, and differentiation to reach all students. According to the teacher, these activities enhance comprehension, auditory and visual skills, and daily English-speaking abilities. Watching short instructional videos also boosts vocabulary and helps teachers explore new methods. Despite their positive impact, audio-visual reading activities pose challenges for teachers, including technical issues (e.g., LCD or speaker problems), time limits, disruptions, and student behavior during videos. However, students enjoy these activities, which enhance their English reading, writing, speaking, and listening skills. Videos, photos, and voice responses improve comprehension, and students’ excitement for reading has increased. They prefer action or animated films over text and can apply new vocabulary in daily conversations. Keywords: Audio-visual, Reading Activity, The Implementation, Teacher’s Perceptions, and Students’ Perspectives.